'Do frogs have a palm?'Behind the scenes of the Norwegian translation of Les soleils des indépendances. (3rd April 2021) - Hesjevoll Schmidt-Melbye, Inger
ABSTRACT: This article discusses challenges found in translator working papers from the process of translating the novel Les soleils des indépendances (Ahmadou Kourouma) into Norwegian. It also draws on interview material connected to the same translation process as well as a scholarly article written by the translator herself, Ingse Skattum. Anchored in the theoretical framework of genetic Translation Studies and the archival turn in Modernist Studies, the present article explores the translator's decision-making by comparing cited passages from the published novel to the same textual issues in the working papers. Furthermore, it displays how the translator is faced with several difficulties that require creativity, a profound knowledge of cultural references, and a pedagogical orientation towards the reader. Thus, this article attempts to shed light upon the translator's constant hesitation between textual alternatives. Using Skattum's multifaceted translation project as a case, the article shows that the idea of the translator's agency should be problematised. The overall aim is to bring attention to the underlying textual process normally invisible to the public and to call for a stronger consciousness and recognition of the translator's complex work among laymen as well as among professionals.